The Quality System in the Industry and Application - الكيال, محمد (Latakia University Journal -Engineering Sciences Series, 2021)
Quality is quality product and goods produced, is that what you mean in the surveillance is to monitor the stages of the production sequence for the production of these goods concerned and the match after the completion of manufacture with the specifications set for them by the production, taking into account the proportion of overtaking either increase or decrease because the stages through which production variable in terms of raw materials and modern machinery complex, not fixed, and the efficiency of any production process determine the extent of match production with what is required in the production of this specification. The identification of any efficiency of any process of production processes and control them in accordance with essential quality control work. And it should be like any program to monitor the quality that means each of the two destinations: the first, which precedes the production in terms of the responsibility of the general specifications and technical goods produced and method of production and the second, which is responsible for matching product specifications with actual specification that is designed on the basis of, The operations include production control back production targets to the necessary steps in order to produce product and determine the materials, tools and human effort and production units necessary also includes determining the time required for each operation and the time expected beginning and the end of the different processes and describe how or itinerary product or commodity and so to do the hard Coordinator and to achieve the desired purpose .